Cell phenotypic change due to Cryptosporidium parvum infection in immunocompetent mice. - Codices, Vera (2017)
Cryptosporidium parvum is an intracellular parasite causing enteritis which can become life-threatening in immunocompromised host. Immunoregulatory T cells play a central role in the regulatory network of the host. Here, we proposed to characterize the populations of immune cells during infection and reinfection with C. parvum. Four-week-old BALB/C mice were inoculated with oocysts of C. parvum at days 0 and 22. Fecal and blood samples, spleens, and small intestines were collected for analysis. Peripheral blood and spleen cell populations were characterized by flow cytometry. After infection (days 0 to 21), mice presented higher values of neutrophils, eosinophils, NK cells and CD4(+)CD25(high) T cells in peripheral blood. After reinfection, this upward trend continued in the following days for all four populations in infected mice. At day 35, infected mice presented similar values to the control group, except for CD4(+)CD25(high) T cells, which remained higher in infected mice. A possible correlation between alterations in blood and spleen cell populations was also studied, but no consistent association could be established. Small intestine sections were screened for intracellular stages of the parasite but no evidence of pathology was observed. Here, we report information which may be important for the understanding of the specific cell-mediated response in immunocompetent mice to C. parvum infection. Although some questions remain unanswered and complementary studies are needed, our results are expected to contribute to a better understanding of innate and Treg cells role in the clearance process of this parasite.